Job Hazard Analysis For Critical Lifting Using Crane in the Oil and Gas Industry - Ab Razak, Muhammad Nur Aiman (Progress in Engineering Application and Technology, 2023)
The lifting activity separated to two categories which were general lifting and critical lifting in some of oil and gas industry. A critical lifting was a rigging activity that required a comprehensive plan to minimize the risk of crane failure or catastrophic loss in the oil and gas industry. Over the past several years, the number of accidents happened in the company was slightly increased from year to year due to various type of operation in there. One of the activities that quite making the number increased was lifting activity. The method used has been shown effectively in result making. Past incident records were used as a reference to differentiate data that has been recorded from year to another year and has been summarize too. The creation of a Job Hazard Analysis (JHA) was the main method used to reduce the risk of accidents happened based on past incident records. This method is further strengthened by the observation on site method. The Job Hazard Analysis form was used to determine how to complete a task step by step, as well as any risks connected to the task and any controls to reduce those risks. As a result, the number of incidents happened during critical lifting activity shows a decrease from year to year. This might be because of several method that has been used to reduce this incident and the implementation of Job Hazard Analysis was the most effective way to used. It was because the Job Hazard Analysis process focuses on four interconnecting relationships which was the worker, task, tools and environment. For the conclusion, the research can be used as a reference to help with problem-solving strategies and the analysis that have been made can support community of safety and health in the oil and gas industry to promote safety and health at the workplace. Finally, this study offers hope for enhancing a positive safety culture at work.